The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1507/endocrj.51.1
|View full text |Cite
|
Sign up to set email alerts
|

Translational Medicine in Fish-derived Peptides: From Fish Endocrinology to Human Physiology and Diseases

Abstract: Abstract. Recent studies have revealed the importance of fish-derived peptide hormones to human endocrinology. These peptides include melanin-concentrating hormone (MCH), urocortins (human urotensin-I), and urotensin-II. MCH, a hypothalamic peptide, is a potent stimulator on appetite. Urocortins, e.g. urocortin 1 and urocortin 3 (stresscopin), are endogenous ligands for the corticotropin-releasing factor (CRF) receptors, particularly CRF type 2 receptor, that mediates a vasodilator action, a positive inotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 160 publications
(146 reference statements)
0
11
0
1
Order By: Relevance
“…Tubular epithelial cells obtained at nephrectomy from patients with diabetic nephropathy showed overexpression of U-II and UT receptor (27). In the presence of diabetes mellitus, U-II may also be associated with obesity (28). Intracerebroventricular administration of U-II into sheep causes hyperglycemia, which may be mediated by U-II-stimulated increases in circulating levels of epinephrine and cortisol (29).…”
Section: Introductionmentioning
confidence: 98%
“…Tubular epithelial cells obtained at nephrectomy from patients with diabetic nephropathy showed overexpression of U-II and UT receptor (27). In the presence of diabetes mellitus, U-II may also be associated with obesity (28). Intracerebroventricular administration of U-II into sheep causes hyperglycemia, which may be mediated by U-II-stimulated increases in circulating levels of epinephrine and cortisol (29).…”
Section: Introductionmentioning
confidence: 98%
“…It also can be found in mammalians central nervous system as a cyclic neuropeptide which has roles in complex network of stress-regulating system and appetite stimulating (Kawauchi et al, 1983;Flier, 2004;. Takahashi et al(2004) have reported salmon and human MCH sequencing ( Fig.1). MCH is stimulator on food intake, may cause to obesity.…”
Section: Melanine-concentrating Hormone (Mch)mentioning
confidence: 99%
“…Urocortins (Ucns) were shown to be expressed in various tissues and cells of the human, such as brain, pituitary, gastrointestinal tract, ovary, placenta, synovial tissue, lymphocytes, and skin [1628]. …”
Section: Discovery Of Urocortinsmentioning
confidence: 99%